METODE LAFZIYAH DALAM MENGISTINBATKAN HUKUM MENURUT MAZHAB ZAHIRIYAH - Siri, Hasnani (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2011)
This article discusses the methods Lafziyah in finding the law. Based on assessment results indicated that schools of az-Zahiriyah is a School that in formulating the law sets only adhered to the rules of language (Mafhun al-Lash). This concept is an alternative development of the law formulated solely by this flow, as a consequence of the rejection method of analogy (analogy). In addition to the Quran and al-Sunnah, this school also uses ijma 'friend and al-proof. The concept of al-effective proposition is deemed to appear to give an answer and a chance to anticipate the complexity of problems that may arise in the community.